Ni(ii) and Co(ii) bis(acetylacetonato) complexes for alkene/vinylsilane silylation and silicone crosslinking. Issue 14 (28th June 2021) - Puillet, Magali; Delorme, James; Crozet, Delphine; Humbert, Matthieu; Gajan, David; Bousquié, Magali; Blanc, Delphine; Raynaud, Jean; Monteil, Vincent
Abstract : Commercially available Ni(ii ) and Co(ii ) complexes – M(acac)2 and M(tmhd)2 – exhibit catalytic activity for alkene/vinylsilane dehydrogenative silylation (DS ) and hydrosilylation (HS ) with tertiary silanes without using any external reducing agents. Abstract : Commercially available Ni(ii ) and Co(ii ) complexes – M(acac)2 (acac = acetylacetonate) and M(tmhd)2 (tmhd = 2, 2, 6, 6-tetramethyl-3, 5-heptanedionato) – exhibit catalytic activity for alkene/vinylsilane dehydrogenative silylation (DS ) and hydrosilylation (HS ) with tertiary silanes without the use of any external reducing agents. Using the model compounds divinyltetramethylsiloxane a.k.a dvtms and vinylpentamethyldisiloxane a.k.a vpmds, different selectivities (HS, DS, undesired non-C–Si bond-forming reactions…) are observed whether nickel or cobalt catalysts are employed, with Ni being DS -selective and Co yielding both HS and DS products. All four complexes are efficient at thermally inducing silicone-oil crosslinking under a non-inert atmosphere, and promote metal-dependent selectivity that is slightly different from model reactions, which HR-MAS NMR spectroscopy unveils. Additional observations as well as NMR studies of [Ni(tmhd)2 + reagent] mixtures provide some insights into the possible activation pathways.